2021
DOI: 10.4236/ajibm.2021.119059
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Improving Customer Loyalty at Retailers in Jeddah City: A Case Study

Abstract: Customers are an integral part of any business; therefore, organizations have to build their customer loyalty in order to achieve long-term profitability. Supermarkets, in their efforts to achieve customer satisfaction, try to be more creative and engaged with their customers in order to get their loyalty. This study aims to explore the relationship between customer satisfaction and customer loyalty in supermarket retailers in Jeddah city, Saudi Arabia. In addition, factors affecting customer loyalty and custo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Loyalty can be described as a condition in which a person purchases products regularly based on decision making (Fuadi et al, 2019). Organizations or companies must strive to be able to provide a very high level of satisfaction and increase the number of loyal customers because customers cause high sales of the latest products and at the same time bind them from competing companies (Alsulami, 2021). Customer loyalty can be achieved from how much the store is willing to provide the best service to customers.…”
Section: Literature Review Customer Loyaltymentioning
confidence: 99%
See 1 more Smart Citation
“…Loyalty can be described as a condition in which a person purchases products regularly based on decision making (Fuadi et al, 2019). Organizations or companies must strive to be able to provide a very high level of satisfaction and increase the number of loyal customers because customers cause high sales of the latest products and at the same time bind them from competing companies (Alsulami, 2021). Customer loyalty can be achieved from how much the store is willing to provide the best service to customers.…”
Section: Literature Review Customer Loyaltymentioning
confidence: 99%
“…Shopping behavior is also influenced by economic factors such as price and promotion.is one of Watsons Indonesia's achievement targets. Customers are an essential source of income for companies (Alsulami, 2021). Loyal customers can provide benefits for the company, for example by not easily switching to other companies with the same product (Nikmah, 2017;Muhammad et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated contradicting arguments in regard to the influence of reward programs on customer buying behavior. A study conducted by Alsulami (2021) explored the relationship between customer satisfaction and customer loyalty in supermarket retailers in Jeddah city, Saudi Arabia. The study employed a survey questionnaire to collect data from a sample of 2000 supermarket customers in the five leading retail supermarkets in Jeddah.…”
Section: Empirical Review and Hypothesis Development Reward Programs ...mentioning
confidence: 99%
“…Many companies have continued to give importance to total promotional package (Agbonifoh et al 2007), because of their competitive role (Onuoha 2016;Agu and Uduak 2018), mainly leading to positive reactions of consumers and driving customer loyalty (Agu 2021;Farris and Quelch 2004;Okpara 2012). Alsulami (2021) conducted a study to identify the customer loyalty of supermarket retailers in Saudi Arabia and found that promotional packages are among the factors that encourage customer loyalty. However, in previous literature based on the telecommunication sector, very few studies considered promotional packages as an antecedent of consumer loyalty, in order to assess the direct or indirect relationship between them in the telecommunication sector (Dhasan and Kowathanakul 2017;Dhasan and Kowathanakul 2021).…”
Section: Promotional Packagementioning
confidence: 99%